Pengaruh Kebijakan Impor Beras Terhadap Kesejahteraan Petani di Kabupaten Klaten - Lia Safitri (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2022)
This article discusses the impact of the rice import policy in Klaten Regency on the welfare of farmers. This study aims to determine the policy of import activities, and to determine the welfare of farmers who are affected by the import of rice. The author uses this type of qualitative research method through library studies